2020
DOI: 10.1186/s12913-020-05238-x
|View full text |Cite
|
Sign up to set email alerts
|

Home care quality indicators based on the Resident Assessment Instrument-Home Care (RAI-HC): a systematic review

Abstract: Background: One way of measuring the quality of home care are quality indicators (QIs) derived from data collected with the Resident Assessment Instrument-Home Care (RAI-HC). In order to produce meaningful results for quality improvement and quality comparisons across home care organizations (HCOs) and over time, RAI-HC QIs must be valid and reliable. The aim of this systematic review was to identify currently existing RAI-HC QIs and to summarize the scientific knowledge on the validity and reliability of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
(91 reference statements)
0
37
0
1
Order By: Relevance
“…At present, there is no the gold standard for comprehensive geriatric assessment as part of the admissions procedure to nursing homes in China. Most nursing in homes in North America and Europe use the Resident Assessment Instrument (RAI), data from which corresponds directly to the frailty index [26], however, such the RAI is currently not utilized in China.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no the gold standard for comprehensive geriatric assessment as part of the admissions procedure to nursing homes in China. Most nursing in homes in North America and Europe use the Resident Assessment Instrument (RAI), data from which corresponds directly to the frailty index [26], however, such the RAI is currently not utilized in China.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that although physical frailty, to some extent, overlapped with disability and comorbidity, many frail participants did not have disability or comorbidity, suggesting that physical frailty did not equate with comorbidity or disability in the population of elderly nursing home residents. At present, there is no the gold standard for comprehensive geriatric assessment which is the standard for admission in the resident assessment instrument among the elderly living in nursing homes in China, therefore, China does not use RAI as that is what is in use in North America and Europe in most nursing homes as the standard and that data can be automatically converted in the frailty index [23].…”
Section: Discussionmentioning
confidence: 99%
“…The RAI-HC QIs are constructed as proportions or percentages, expressed by a fractional calculation with numerator (number of clients with a particular outcome) and denominator (number of clients at risk for the outcome and not otherwise excluded from the QI) [ 5 , 21 ]. A systematic review showed that currently 48 RAI-HC QIs exist [ 22 ]. These QIs cover different areas relevant to home care, focusing on functional (e.g.…”
Section: Introductionmentioning
confidence: 99%